Virus-Induced Asthma Exacerbations: SIRT1 Targeted Approach - Fukuda, Yosuke (J Clin Med, 2020)
The prevalence of asthma has increased worldwide. Asthma exacerbations triggered by upper respiratory tract viral infections remain a major clinical problem and account for hospital admissions and time lost from work. Virus-induced asthma exacerbations cause airway inflammation, resulting in worsening asthma and deterioration in the patients’ quality of life, which may require systemic corticosteroid therapy. Despite recent advances in understanding the cellular and molecular mechanisms underlying asthma exacerbations, current therapeutic modalities are inadequate for complete prevention and treatment of these episodes. The pathological role of cellular senescence, especially that involving the silent information regulator 2 homolog sirtuin (SIRT) protein family, has recently been demonstrated in stable and exacerbated chronic respiratory disease states. This review discusses the role of SIRT1 in the pathogenesis of bronchial asthma. It also discusses the role of SIRT1 in inflammatory cells that play an important role in virus-induced asthma exacerbations. Recent studies have hypothesized that SIRT1 is one of major contributors to cellular senescence. SIRT1 levels decrease in Th2 and non-Th2-related airway inflammation, indicating the role of SIRT1 in several endotypes and phenotypes of asthma. Moreover, several models have demonstrated relationships between viral infection and SIRT1. Therefore, targeting SIRT1 is a novel strategy that may be effective for treating virus-induced asthma exacerbations in the future.